Research uptake management: a strategic framework for institutionalising research uptake at the Kwame Nkrumah University of Science and Technology, Kumasi - Ankamah-Lomotey, Vincent Anum (Stellenbosch : Stellenbosch University, 2019)
Thesis (PhD)--Stellenbosch University, 2019.